Macroeconomic factors and antidumping filings: Evidence from four countries - Michael M. Knetter; Thomas J. Prusa (Rutgers University, Department of Economics, 2000)
This paper examines the relationship between antidumping filings and macroeconomic factors. We show that real exchange rate fluctuations affect the two criteria for dumping in opposite ways, making the overall effect on filings ambiguous in theory. Interestingly, no such ambiguity is evidenced in the data. Examining the filing patterns of the four major users of AD law during the 1980–98 period we find that real exchange rates and domestic real GDP growth both have statistically significant impacts on filings. Bilateral filing data indicate that a one-standard deviation real appreciation of the domestic currency increases filings by 33% while a one-standard deviation fall in domestic real GDP increases filings by 23%.
Keywords: F13; 330; antidumping law; exchange rate pass-through; Antidumping; Kaufkraftparität; Wirtschaftswachstum; Australien; USA; Kanada; EU-Staaten